Strengthening Health Cadre Capasity in Tb Detection: Evaluation in Urban South Jakarta - Rina Kurniasri Kusumaratna; Suriyani Tan; Mutiara Indah Sekar Sari; Mutiara Sri Rahayu; Ranna Adjani Herteniza; Risna Muthmainnah Riskawa (Universitas Malahayati Lampung, 2026)
ABSTRACT Proper TB management hinges on three key aspects: early diagnosis, early detection of drug resistance, and prompt initiation of treatment plans. Mobilizing the community to actively participate in TB screening activities conducted by health facilities is crucial. Enhancing the knowledge and skills of health cadres is necessary to enable them to independently and support health workers in community TB screening efforts. This activity aims to evaluate, assess and address issues, improve TB case detection and treatment, and empower health cadres to become TB champions, accelerating the elimination of tuberculosis, in Pasar Minggu sub-district, South Jakarta. Results indicate that the education and training activities effectively enhanced cadres' TB screening and contact investigation skills. Post-test assessments showed significant (p0.05) improvement in understanding and abilities, with average scores rising considerably from 78.67 (pre-test) to 98.67 (post-test), confirming successful knowledge and skill acquisition. Health cadres identified five new cases through home visits during active case-finding and contact investigation efforts. Engaging the community is crucial for effective public health interventions, ensuring both relevance and practical implementation. Keywords: Skill Development, Tuberculosis Management, Community Involvement.